THU0246 Procalcitonin Test in the Differential Diagnosis of Infections and Rheumatic Diseases. (9th June 2015) - Belov, B.S.; Tarasova, G.M.; Aleksandrova, E.N.; Novikov, A.A.
Abstract : Background: Estimation of serum procalcitonin (PCT) levels is of great interest in rheumatology for both the diagnosis of co-infections and the differential diagnosis between rheumatic disease activity and the current infectious process. Objectives: To estimate the value of PCT as a specific marker for generalized and local infection in rheumatic patients. Methods: A retrospective study of the case histories of 100 inpatients was performed. Serum PCT concentrations were determined by a quantitative electrochemiluminescence assay using a Cobas E 411 analyzer (Roche, Switzerland). Results: Infectious diseases were diagnosed in 41 of the 100 patients. The infectious process was generalized and local in 11 and 30 cases, respectively. In patients with generalized infection, the level of PCT was more than 2.0 ng/ml in 81.8% of the cases. In cases of local infection and non-infection groups, it was below 0.5 mg/ml in 70% and 84.7% of cases, respectively. In the generalized infection group, the content of PCT was significantly higher than in local infection (p=0.004) and non-infection (p=0.0001) groups (table ). It did not depend on rheumatic disease activity. C-reactive protein levels and erythrocyte sedimentation rate correlated with PCT concentrations in different patient groups. ROC analysis showed the optimal sensitivity (82%) and specificity (98%) of PCT as a marker of systemic infection only in rheumatic patients with its concentration of ≥2.3 ng/ml. Thus the positive predictive value was 0, 9. This shows high clinical informativeness of the test. Conclusions: PCT evaluation can be used to facilitate the diagnosis of generalized infections and the differential diagnosis of systemic rheumatic diseases and infectious ones. But PCT results must be interpreted considering available symptom complex and additional examination data. Questions of PCT cut off points determination are worthy of further examination in prospective comparative studies. Disclosure of Interest: None declared